2014
DOI: 10.3892/etm.2014.1729
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide induces apoptosis of breast cancer cells via a mechanism associated with the Wnt/β-catenin signaling pathway

Abstract: Triptolide is a diterpene triepoxide compound extracted from the medicinal plant, Tripterygium wilfordii Hook F. The aim of the present study was to determine whether triptolide inhibits the proliferation of breast cancer cells and to further investigate the associated molecular mechanisms. The effects of triptolide on the cell viability of three breast cancer cell lines, specifically, highly metastatic MDA-MB-231, human epidermal growth factor receptor 2-positive BT-474 and estrogen receptor-positive MCF7 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…The results indicated that the Wnt pathway participated in the development of vascular mimicry and cell proliferation induced by shRNA-Pygo2. Previous studies have also transfected the siRNA sequences specific to Pygo protein mRNA, and inhibited the TCF/LEF-mediated transcriptional activation of reporter genes (30,31), which suggested that Pygo2 members may be involved in TCF/β-catenin-driven transcription. In the present study, the expression of cyclin D1 protein in the U251 cells treated with shRNA-Pygo2 was investigated.…”
Section: A B Cmentioning
confidence: 99%
“…The results indicated that the Wnt pathway participated in the development of vascular mimicry and cell proliferation induced by shRNA-Pygo2. Previous studies have also transfected the siRNA sequences specific to Pygo protein mRNA, and inhibited the TCF/LEF-mediated transcriptional activation of reporter genes (30,31), which suggested that Pygo2 members may be involved in TCF/β-catenin-driven transcription. In the present study, the expression of cyclin D1 protein in the U251 cells treated with shRNA-Pygo2 was investigated.…”
Section: A B Cmentioning
confidence: 99%
“…Previously triptolide was reported to attenuate Wnt3a-CM-induced β-catenin protein levels in a dose dependent manner1317. We examined whether triptonide has a similar effect on β-catenin levels using the active non-phosphorylated β-catenin antibody.…”
Section: Resultsmentioning
confidence: 99%
“…The associated molecular mechanisms by which TPL inhibits breast cancer cells have been investigated. n In breast cancer, TPL induces p53-dependent and lysosomal-mediated apoptosis, and inhibits numerous oncogenic signaling pathways, including the Wnt/β-catenin, the protein kinase B (Akt) and the focal adhesion kinase-signaling pathway (3,10,11). Notably, TPL inhibits key transcriptional factors, including MYC and estrogen receptor (ER), which suppresses associated target networks (12,13).…”
Section: Introductionmentioning
confidence: 99%